Teologi Resolusi Konflik dalam Tafsir al-Maraghi: Rekonstruksi Epistemologis untuk Menghadapi Polarisasi Digital - Zukhruf Hafiz Rahimi; Sugeng Wanto (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the paradigm of conflict resolution in Tafsir al-Maraghi and reconstructs its epistemological relevance for addressing digital polarization. Employing a qualitative library research design with the thematic (maudhu'i) method of Qur'anic exegesis, the study analyzes key Qur'anic verses on conflict resolution interpreted by Ahmad Mustafa al-Maraghi and conceptually tests them against three contemporary cases of digital conflict: religious disinformation related to the Gaza conflict, religious identity polarization during Indonesia's 2024 presidential election, and the spread of takfiri preaching on TikTok. The findings reveal that al-Maraghi's conflict resolution paradigm is built upon five interconnected principles: al-'adl wa al-qist (justice), al-hiwar wa al-musyawarah (dialogue and consultation), al-'afw wa al-islah (forgiveness and reconciliation), al-sabr wa al-i'tidal (patience and moderation), and al-ta'awun 'ala al-birr (cooperation for righteousness). These principles demonstrate strong conceptual relevance in explaining and responding to patterns of digital conflict, particularly in fostering critical verification, dialogue, reconciliation, moderation, and social solidarity. Nevertheless, the paradigm remains limited in addressing structural issues such as algorithmic amplification, political power relations, digital platform governance, and the emergence of generative artificial intelligence. This study concludes that al-Maraghi's paradigm should be positioned as an ethical and epistemological foundation rather than a standalone solution, requiring integration with technological governance and public policy to effectively address contemporary digital conflicts.